2022
DOI: 10.1101/2022.03.01.482495
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An antisense oligonucleotide-based strategy to ameliorate cognitive dysfunction in the 22q11.2 Deletion Syndrome

Abstract: Up-regulation of Mirta22/Emc10 is a major transcriptional effect of the 22q11.2-associated microRNA dysregulation and underlies key cellular as well as behavioral deficits. EMC10 is a component of the ER membrane complex, which promotes membrane insertion of a subset of polytopic and tail-anchored membrane proteins. Here we show that EMC10 expression is elevated in hiPSC-derived neurons from 22q11.2 deletion carriers and that reduction of EMC10 levels restores defects in neurite outgrowth and calcium signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 100 publications
1
4
0
Order By: Relevance
“…We also tested whether there are alterations in neuronal activity in patient compared to control organoids using as a proxy system-wide glutamate-induced Ca 2+ transients. Comparisons of three pairs at day 259 identified a significant decrease in Ca 2+ peak amplitude in case compared to control cells ( P = 5.78×10 -12 , average number of cells per organoid: n=89 patient, n=124 control, Fig 1c,d,e ) consistent with previous findings in monolayer cultures of both mouse and patient neurons 12,13,14 . Thus, despite the lack of overt effects in growth, patient organoids display different functional properties, validating their usefulness as a preclinical model for studying the disease mechanisms underlying 22q11.2 deletions.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…We also tested whether there are alterations in neuronal activity in patient compared to control organoids using as a proxy system-wide glutamate-induced Ca 2+ transients. Comparisons of three pairs at day 259 identified a significant decrease in Ca 2+ peak amplitude in case compared to control cells ( P = 5.78×10 -12 , average number of cells per organoid: n=89 patient, n=124 control, Fig 1c,d,e ) consistent with previous findings in monolayer cultures of both mouse and patient neurons 12,13,14 . Thus, despite the lack of overt effects in growth, patient organoids display different functional properties, validating their usefulness as a preclinical model for studying the disease mechanisms underlying 22q11.2 deletions.…”
Section: Resultssupporting
confidence: 89%
“…We first examined the dysregulation of microRNAs (miRNAs) as a potential mechanism for the asynchronous expression of maturation-associated genes. We have previously shown that 22q11.2 deletion results in brain-enriched miRNA downregulation and an upregulation in target gene expression due to (i) hemizygosity of DGCR8 27,28 , a component of the “microprocessor” complex that is essential for miRNA production and (ii) hemizygosity of miRNA genes residing within the deletion 12,28, 29 . To assess the contribution of miRNA dysregulation to our observed cellular and RNA-seq phenotypes we performed bulk miRNA sequencing on suspension from 3 pairs of 8-10 DIV70 organoids.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations